Factors Associated With Substance Use Among Senior High School Students On Bushrod Island, Montserrado County, Liberia - Sherman, H.M. (University Of Ghana, 2020)
Introduction World Health Organization defines substance as “a material that alters a person’s mood, perception, or cognitive behavior when it is smoked, injected, swallowed, drunk, inhaled in powder, or vapor”. The use of such psychoactive substances can lead to dependence syndrome which is a thicket of a behavioral, and physiological effect that evolves after sequential use. Methods This study employs a cross-sectional design, using a quantitative approach to gather data on substance use among senior high school students in Bushrod Island, Montserrado county. We adapted the 2012 Global School-based Student Health Survey questionnaire and used it to collect the data through Kobo collect ®(odk) platform. Data was downloaded in Excel 2016, format and analyzed by using Stata version 15 statistical software. The result of the analysis was presented as frequency tables with percentages, and charts. To investigate factors associated with adolescent substance use, cross-tabulations with Pearson's chi-square tests, bivariate and multivariate analyses (logistic regression) were used. Results Of the 402 students surveyed, 291 (72.4%) had ever used a substance before, were males and, those between the ages of 19 to 21 years were 298 (74.1%). Alcohol was the most commonly used substance 255 (87.6%). The majority of students, 332 (83.4%) indicated that they currently used a substance. The age at first time use of a substance was reported as 18 to 20years in 147 (36.9%) of the students. Risk factors associated with alcohol and drug use include alcohol availability and the only mother as guardian appear to justify the risk of student alcohol and drug use. Conclusion The most used substance was alcohol and the prevalence of substance use among SHS students was high in Liberia. Most of the substances used among SHS students were identified to be alcohol, Marijuana, cocaine, and tobacco (cigarettes), so the results of our data advise that an engagement should be made to cut down the availability of alcohol use.
MPH
Keywords: Liberia; Montserrado County; Senior High School; Substance